Development of a Virtual Three‐Dimensional Assessment Scenario for Anatomical Education. Issue 3 (5th March 2021) - Bogomolova, Katerina; Sam, Amir H.; Misky, Adam T.; Gupte, Chinmay M.; Strutton, Paul H.; Hurkxkens, Thomas J.; Hierck, Beerend P.
Abstract : In anatomical education three‐dimensional (3D) visualization technology allows for active and stereoscopic exploration of anatomy and can easily be adopted into medical curricula along with traditional 3D teaching methods. However, most often knowledge is still assessed with two‐dimensional (2D) paper‐and‐pencil tests. To address the growing misalignment between learning and assessment, this viewpoint commentary highlights the development of a virtual 3D assessment scenario and perspectives from students and teachers on the use of this assessment tool: a 10‐minute session of anatomical knowledge assessment with real‐time interaction between assessor and examinee, both wearing a HoloLens and sharing the same stereoscopic 3D augmented reality model. Additionally, recommendations for future directions, including implementation, validation, logistic challenges, and cost‐effectiveness, are provided. Continued collaboration between developers, researchers, teachers, and students is critical to advancing these processes.